Sensitivity of postnatal fasting plasma glucose in identifying impaired glucose tolerance and frank diabetes in women with gestational diabetes. (18th April 2012) - Yeeles, H; Madhuvrata, P; Bustani, R; Farrell, T
Abstract : Aims: To review postnatal glucose tolerance testing (GTT) in women with gestational diabetes mellitus (GDM) and to determine whether there is an essential role for 2 hour GTT in screening for both impaired glucose tolerance and type 2 diabetes. Methods: All women with gestational diabetes diagnosed between January 2008 and June 2011 were included. Patients were offered a post-natal GTT at 6 weeks after delivery. Fasting blood glucose results were compared to the results of 2 hours post glucose challenge. Results: The total number of women with GDM was 811. 191 (24%) women declined or failed to attend their post-natal GTT. 71 (11%) had an abnormal result. Of this, 14 were diagnosed with type 2 diabetes and 57 with impaired glucose tolerance (IGT). 42 (40 IGT and 2 type 2 diabetes) of these with abnormal GTT had fasting glucose ≤6 mmol/l. A fasting glucose of ≥6.1mmol/l correctly identified 29 of 71 cases of abnormal GTT, with a sensitivity of 40%. Sensitivity 40%, specificity 94%, PPV 50%, NPV 92% Conclusions: Impaired post-natal glucose tolerance has both implications for future pregnancies and long term health. It is also a strong predictor of developing type 2 diabetes. Formal diagnosis, education and subsequent management is therefore essential. GTT is crucial in identifying these patients, since fasting blood glucose alone is not sufficiently sensitive.